The impact of contact with nature on positive youth development: a multiple mediation model - Yulan Li; Liling Mo; Caiyan Tan; Jin Fu; Jin Fu; Niyan Wang (Frontiers in Psychology)
IntroductionIn recent years, there has been increasing evidence supporting the benefits of contact with nature. Little is known about the mechanisms of how nature contact lead to these benefits. Positive youth development refers to the state in which adolescents strive to achieve full, healthy, and successful growth, which has been an important goal for societies. Against this background, the present study aimed to examine whether and how adolescents’ contact with nature influences positive youth development in a sample of Chinese adolescents.MethodsDrawing on the biophilia hypothesis, stress recovery theory, and attention restoration theory, 1,730 junior high school students participated in a questionnaire survey. The study employed a multiple mediation model to explore the effects of adolescents’ contact with nature on positive youth development, mediated through mindfulness, connectedness to nature, and perceived stress.ResultsAdolescents’ contact with nature positively predicted the level of positive youth development, while contact with artificial environments did not. Contact with nature not only directly predicted the level of positive youth development but also indirectly influenced it through the mediating effects of connectedness to nature and perceived stress, but the mediated effect of mindfulness was no significant.DiscussionThese findings provide empirical support for the biophilia hypothesis and stress recovery theory. They also have important implications for urban planning and school policies, suggesting that ensuring adolescents have access to and opportunities to engage with natural environments is crucial for promoting positive youth development.